Controlled-Release Low Density Effervescent Floating Matrix Tablets of Risperidone: Development, Optimization, in vitro-in vivo Evaluation in Healthy Human Volunteers and Determination of Dissolution Equivalency: Formulation and evaluation of floating matrix tablet of Risperidone in human volunteer - Muhammad Imran,; Nazar Muhammad Ranjha,; Rao Khurram Ayoub, (Iranian Journal of Pharmaceutical Sciences, 2013)
The main objective of the present study was to formulate gastroretentive effervescent sustained release drug delivery systems of risperidone floating tablets with the help of Methocel® K15, Ethocel® standard 7FP premium, Eudragit ® RS100 sustained release polymers to improve its safety profile, bioavailability and patient compliance. Risperidone floating tablets were formulated by wet granulation technique by using citric acid and sodium bicarbonate as a gas generating agent. Methocel® K15, Ethocel® standard 7FP premium, Eudragit® RS 100 were used to formulate floating effervescent sustained release tablets. Preliminary trials were done to investigate matrix integrity and floating behavior. On the basis of preliminary trials, various formulations were designed to optimize the best formulation. The FDA recommended statistical approach was used to test dissolution equivalency. Preliminary studies showed better floating behavior, but poor matrix integrity with Methocel®K15 containing formulations. Moreover, Ethocel® standard 7FP premium and Eudragit® RS 100 containing formulations showed better matrix integrity but poor floating behavior. Formulations RSFTIII, RSFTVI, RSFTIX were optimized and showed the drug release for 10 hours. Dissolution equivalency was tested for optimized formulation and found equivalent. In vivo-study also showed gastric retention time more than 4 hours.